Pengaruh Media Pembelajaran E-Modul Berbasis Sigil Terhadap Motivasi Belajar Siswa pada Mata Pelajaran Desain Grafis - Putri, Melgi Andari; Purmadi, Ary (Jurnal Teknologi Pendidikan : Jurnal Penelitian dan Pengembangan Pembelajaran, 2020)
The purpose of this study was to analyze the effect of sigil-based e-module learning media on student learning motivation in graphic design subjects in class X Multimedia at SMKN 1 Lingsar. The research method used was experimental. This study used a population of 36 students. The data collection methods used in this study were questionnaires, observation and documentation. The data analysis technique used statistical analysis with the chi square formula. The results of the analysis obtained the value = 12.462 while the chi square value in the table with db = 4 with a significance level of 5% = 9.488 so that the value of the chi square analysis is greater than the value of the chi square table (12.462> 9.488). So it can be concluded that there is an effect of sigil-based e-module learning media on student learning motivation in graphic design subjects in class X Multimedia at SMKN 1 Lingsar.